Efektivitas Pembelajaran Matematika Bermuatan TPACK Materi Pecahan Kelas V Sekolah Dasar Negeri 12 Pontianak Selatan - Venia Etma Avissa; Hamdani Hamdani; Rio Pranata (Journal on Education, 2023)
This study aims to determine the effectiveness of mathematics learning with TPACK on fraction material in class V of State Elementary School 12 South Pontianak. The type of research used is descriptive research with quantitative descriptive method. The subjects in this study were students of grade V of State Elementary School 12 South Pontianak, totaling 37 students. The data collection techniques used in this study were observation, questionnaire, and documentation techniques. The data collection tools used were observation sheets, questionnaire sheets, and student learning outcomes data. The results showed that students' learning activities were classified as active with an average percentage of 76.47%, then the responses given by students during the learning process were also very positive with an average percentage of 93.28%, the percentage of classical student learning outcomes was 86.49%, and teacher performance in implementing learning averaged 8.26 and was in the very good category. Learning is said to be effective if it meets the minimum criteria of the four aspects. Because the four aspects have met the minimum criteria determined, it can be concluded that mathematics learning with TPACK on fraction material is effective in class V of State Elementary School 12 South Pontianak.